BLENDED LEARNING APPROACHES IN ENGLISH CLASSROOMS - Muxtorova Farangiz Shuhratjon qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Blended learning has become one of the most effective ways to teach English in today’s classrooms. It combines traditional in-person instruction with digital tools and online learning platforms, giving students more flexibility and opportunities to engage. This paper explores how blended learning works in English as a Foreign Language (EFL) settings, especially in Uzbekistan, where technology and education are both developing quickly. It discusses how this approach benefits both teachers and learners, what challenges schools might face, and what steps can make implementation more successful. The study concludes that when used thoughtfully, blended learning can create a more inclusive, flexible, and motivating learning environment.